Answer:
f(x) =
![(-h(x) + 7)/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ubgz0net7k5mbbbditt68hbwomde88e65w.png)
Explanation:
h(x) is defined by the formula,
h(x) = -4f(x) + 7
If the graph attached is of the function 'h' and we have to find the function 'f',
h(x) - 7 = -4f(x)
4.f(x) = -h(x) + 7
f(x) =
![(-h(x) + 7)/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ubgz0net7k5mbbbditt68hbwomde88e65w.png)
Therefore, function 'f' will be defined by,
f(x) =
![(-h(x) + 7)/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ubgz0net7k5mbbbditt68hbwomde88e65w.png)